2023
DOI: 10.3390/pharmaceutics15041297
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative and Osteogenic Supportive Effect of VEGF-Loaded Collagen-Chitosan Hydrogel System in Bone Marrow Derived Mesenchymal Stem Cells

Abstract: The use of hydrogel (HG) in regenerative medicine is an emerging field and thus several approaches have been proposed recently to find an appropriate hydrogel system. In this sense, this study developed a novel HG system using collagen, chitosan, and VEGF composites for culturing mesenchymal stem cells (MSCs), and investigated their ability for osteogenic differentiation and mineral deposition. Our results showed that the HG loaded with 100 ng/mL VEGF (HG-100) significantly supported the proliferation of undif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 69 publications
1
9
0
1
Order By: Relevance
“…In the current study, the proliferation stimulative effect of VEGF was no longer significant after the cell differentiation was initiated on around day 14. This current observation is consistent with the results in other studies also reporting that cell proliferation declines after two weeks of the osteogenic induction [46,52,53]. Both the hydrogels, with and without liposomes groups, exhibited higher ALP activities than the OM and OM + VEGF groups, consistent with the findings by Takagishi et al (2006) [54], in which the promotion of osteogenic differentiation was reported in MG-63 cells cultured on gelatin hydrogels.…”
Section: Effects Of Liposomal Hydrogel On Cell Viability Differentiat...supporting
confidence: 93%
See 4 more Smart Citations
“…In the current study, the proliferation stimulative effect of VEGF was no longer significant after the cell differentiation was initiated on around day 14. This current observation is consistent with the results in other studies also reporting that cell proliferation declines after two weeks of the osteogenic induction [46,52,53]. Both the hydrogels, with and without liposomes groups, exhibited higher ALP activities than the OM and OM + VEGF groups, consistent with the findings by Takagishi et al (2006) [54], in which the promotion of osteogenic differentiation was reported in MG-63 cells cultured on gelatin hydrogels.…”
Section: Effects Of Liposomal Hydrogel On Cell Viability Differentiat...supporting
confidence: 93%
“…The findings of the current study showed that the effect of sustained delivery of VEGF from liposomal hydrogel was the most superior compared with the hydrogel without liposomes carrier system reported by Wu et al (2019) [45] and Elango (2023) [46], as well as the bolus delivery of VEGF without carrier [47]. This is explained by the sustained delivery of VEGF over the 21-day culture period.…”
Section: Effects Of Liposomal Hydrogel On Cell Viability Differentiat...mentioning
confidence: 64%
See 3 more Smart Citations